Patient-Centered Safety Outcomes After Hysteroscopic Compared With Laparoscopic Sterilization. Issue 3 (March 2022) - Gariepy, Aileen M.; Lewis, Carrie; Zuckerman, Diana; Tancredi, Daniel J.; Murphy, Eryn; McDonald-Mosley, Raegan; Sonalkar, Sarita; Hathaway, Mark; Nunez-Eddy, Claudia; Schwarz, Eleanor Bimla
Abstract : OBJECTIVE: To evaluate the real-world safety of hysteroscopic compared with laparoscopic surgical sterilization. METHODS: We conducted a retrospective cohort study of Medicaid claims for hysteroscopic or laparoscopic sterilization procedures performed in California, 2008–2014, among women aged 18–50 years. After excluding postpartum procedures, we applied log-linear (Poisson) event-history regression models for clustered person-period data, weighted for propensity to receive either sterilization procedures, and adjusted for sociodemographic and clinical characteristics that may affect outcomes of interest to patients and physicians. We assessed the following outcomes: procedural complications, additional surgical procedures (eg, hysterectomy), repeat sterilization procedures, pelvic pain, pelvic inflammatory disease (PID), abdominal pain, nonabdominal pain, and abnormal uterine bleeding. RESULTS: We identified 5, 906 women who had undergone hysteroscopic and 23, 965 who had undergone laparoscopic sterilization. After adjusting for sociodemographic and health history, women who had hysteroscopic sterilization were less likely to have claims for procedural complications (eg, transfusion, P <.001) on the day of surgical sterilization and additional surgical procedures (eg, hysterectomy, P =.002 at day 2–3 months postprocedure) than laparoscopic sterilization. Claims for a repeat attempt at sterilization were more common after hysteroscopic sterilization within 1 year (adjusted incident rate ratio 3.48, 95% CI 2.69–4.27) and within 5 years (adjusted incident rate ratio 2.32, 95% CI 1.84–2.79) than laparoscopic sterilization. Claims for pelvic pain (adjusted incident rate ratio 0.77, 95% CI 0.65–0.92 at 2 years), abdominal pain (adjusted incident rate ratio 0.80, 95% CI 0.68–0.93 at 7–12 months), and PID (adjusted incident rate ratio 0.55, 95% CI 0.33–0.93 at 2 years) were less common after hysteroscopic than laparoscopic sterilization. Although abnormal uterine bleeding claims were more common after hysteroscopic than laparoscopic sterilization up to 12 months postprocedure (adjusted incident rate ratio 1.37, 95% CI 1.06–1.77 at 7–12 months), there were no significant differences between methods 1 year after the procedure. CONCLUSION: Compared with laparoscopic sterilization, hysteroscopic sterilization was followed by more claims for repeat sterilization procedures and abnormal uterine bleeding, but fewer procedural complications and fewer claims for pelvic or abdominal pain. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT03438682. Abstract : Compared with laparoscopic sterilization, hysteroscopic sterilization was followed by more claims for repeat sterilization procedures and abnormal uterine bleeding but fewer claims for pelvic or abdominal pain.